Conceptual Study of Role of Gandhakadi Malahara In Dadru - Tripathi, Dr. Akanksha; Singh, Dr. Op; Tripathi, Dr. Sanjay Kumar; Kala, Dr. Jaya Saklani (RA Journal of Applied Research, 2021)
Dadru is one of the common skin diseases mentioned in Ayurveda. In Ayurveda Twak Sharir holds important place. Ayurvedic literatures have described Twak Sharir with various types of Kushtha according to layers of skin. Dadru is a type of Kushtha which mainly affects the 4th layer among the six layers of the skin. In modern science the clinical manifestation of Dadru is closely related to local fungal/tinea infection which is affecting upto 15% of population. Excessive severe itching and ring shaped red patches are the common manifestation which can be diagnosed by Darshana and Prashana Pariksha. Management includes Shodhan, Shaman and Bahirparimarjan Chikitsa. Among them Shaman measures in the form of Lepa (topical applications) are widely prescribed. In present study Gandhakadi Malhar is selected as Topical application.